Impact of Wearable Healthcare Devices on Heathcare Outcomes: A Systematic Review - Nasser Abdullatif Ruhaydin Aloufi; Mohammed Fadhi Inayah Allah Alharbi; Bandar Seraj Omar Alsubyani; Raed Ali Mohammed Wasili; Bsaam Adel Mohammed shafiq Meena; Nemer Saadi Saud Aloufi; Abdulaziz Khalaf Mohammed Alkhathami (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare delivery in general, chronic illness management, and preventive care are all impacted by the incorporation of wearables into healthcare ecosystems. Providing a thorough understanding of the various facets of wearables’ involvement in healthcare is the goal of this review. It examines the many types of wearables, from smartwatches and fitness trackers to specialist medical wearables, explaining their features and possible uses in medical environments. This present study evaluates the scenario in the light of studies conducted in the recent past and present them in the form of a review. The time period of review is 2014 to 2024. most of the studies are related to point in question and provide details about the wearable healthcare devices and their respective outcomes.